Managing Power Sharing of the State on Islamic Modern Society: a Case Study of Indonesia - Ibnu Sina Chandranegara; Rantawan Djanim (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2019)
Abstract - On reasearch "checks and balances" in legal studies often raises high quality questions such as, does the checks and balances is a doctrine, principle, or legal theory, or maybe precisely the formula of power in politics. History been recorded, that in any discussions regarding the formation of the constitutional separation, division and smelting power is something that is popular to be discussed before and even after becoming the constitution. Therefore, the casting of checks and balances into the constitution especially on islamic modern society is an interesting study to determine the portion and posture. This study will use Indonesia legal system and its Islamic Society as case study and will be using legal normative methodoloy, on the other hand, comparative studies on constitution which will be conducted and using classic and modern constitutional law literature. Several approach will be use on this research such as, historical, political, economical approach on understanding the practice on checks and balance which pouring in constitutions in some countries.Keywords - Checks and balances, Politics and Constitution, Separation Power